2016
DOI: 10.48550/arxiv.1603.09415
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

WiSPA: A new approach for dealing with widespread parasitism

Abstract: Traditionally, studies of coevolving systems have considered cases where a parasite may inhabit only a single host. The case where a parasite may infect many hosts, widespread parasitism, has until recently gained little traction. This is due in part to the computational complexity involved in reconstructing the coevolutionary histories where parasites may infect only a single host, which is NP-Hard. Allowing parasites to inhabit more than one host has been seen to only further compound this computationally in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…We used the default cost model (zero for cospeciation, one for duplication, two for duplication and host‐switch, one for symbiont losses, and one for failure to diverge) (Conow et al, 2010 ). A spread event is common among pathogens that can infect multiple phylogenetically distantly related hosts (Drinkwater et al, 2018 ). However, spread is not covered by current event‐based methods due to its computational complexity (Charleston & Libeskind‐Hadas, 2014 ; Drinkwater et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the default cost model (zero for cospeciation, one for duplication, two for duplication and host‐switch, one for symbiont losses, and one for failure to diverge) (Conow et al, 2010 ). A spread event is common among pathogens that can infect multiple phylogenetically distantly related hosts (Drinkwater et al, 2018 ). However, spread is not covered by current event‐based methods due to its computational complexity (Charleston & Libeskind‐Hadas, 2014 ; Drinkwater et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our results also showed that there were nine failure to diverge events, where the orchid has failed to speciate in parallel with divergence in the fungi. However, an alternative explanation, which is not captured in current event-based analyses due to computational difficulties (Charleston & Libeskind-Hadas, 2014;Drinkwater et al, 2018), is that the orchids have experienced "spread" events (Drinkwater et al, 2018;Fraija-Fernández et al, 2016), whereby orchid species have retained their original fungal species but then also Host-switching occurs when a duplication event of the orchid is followed by one of the two sister orchid species switching to a fungus that belongs to a different clade in the fungus phylogeny (Charleston & Perkins, 2006;Conow et al, 2010). Host-switching is not prevalent for Drakaea and Chiloglottis (no events identified), but appears to have occurred more frequently for the fungal associations of Arthrochilus (two events).…”
Section: Which Evolutionary Events Predominate In the Drakaeinae-tula...mentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, the parsimony-based methods that address multiple associations are the following: CoRe-Pa (Merkle et al, 2010), Jane 4 (Conow et al, 2010) and WiSPA (unpublished, see Drinkwater et al (2016)). The tool CoRe-Pa (Merkle et al, 2010) deals only with the case of cryptic species and solves the multiple associations locally in a parsimonious way.…”
Section: Introductionmentioning
confidence: 99%
“…The tool CoRe-Pa (Merkle et al, 2010) deals only with the case of cryptic species and solves the multiple associations locally in a parsimonious way. Jane 4 (Conow et al, 2010) and WiSPA (Drinkwater et al, 2016) consider multiple associations as resulting only from recent host switches (case (iii) above, see Brooks et al (2004)).…”
Section: Introductionmentioning
confidence: 99%